Burning Water, Overview of the Contribution of Arjen Hoekstra to the Water Energy Nexus - Winnie Gerbens-Leenes (Water, 2020)
This paper gives an overview of the contribution of water footprint (WF) studies on water for energy relationships. It first explains why water is needed for energy, gives an overview of important water energy studies until 2009, shows the contribution of Hoekstra’s work on WF of energy generation, and indicates how this contribution has supported new research. Finally, it provides knowledge gaps that are relevant for future studies. Energy source categories are: 1. biofuels from sugar, starch and oil crops; 2. cellulosic feedstocks; 3. biofuels from algae; 4. firewood; 5. hydropower and 6. various sources of energy including electricity, heat and transport fuels. Especially category 1, 3, 4, 5 and to a lesser extent 2 have relatively large WFs. This is because the energy source derives from agriculture or forestry, which has a large water use (1,2,4), or has large water use due to evaporation from open water surfaces (3,5). WFs for these categories can be calculated using the WF tool. Category 6 includes fossil fuels and renewables, such as photovoltaics and wind energy and has relatively small WFs. However, information needs to be derived from industry.